Fungsi Sosial Tuturan Mitos Kehamilan pada Masyarakat Jawa di Malang Selatan - Susita Rahayu; Hari Windu Asrini (CV. Alim's Publishing, 2026)
This study discusses the social functions of speech in pregnancy myths within the Javanese community of South Malang through a sociolinguistic perspective. The purpose of this study is to describe the forms of social functions found in pregnancy myth utterances and the sociolinguistic meanings contained within them. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research data were in the form of oral utterances delivered by mothers, grandmothers, elders, husbands, and traditional birth attendants to pregnant women. The results of the study indicate that pregnancy myth utterances have four social functions, namely educational, regulative, protective, and cultural inheritance functions. The protective function is the most dominant because most utterances contain prohibitions and advice aimed at protecting pregnant women and unborn babies from physical, psychological, and spiritual risks. Pregnancy myth utterances reflect the close relationship between language, culture, belief systems, and the social life of the Javanese community in South Malang, which has been passed down from generation to generation.